Effect of submucosal alcohol injection on prolonged rectal prolapse in infants and children - Bahador Ali; Foroutan Hamid; Hosseini Seyed; Davani Sam (Wolters Kluwer Medknow Publications, 2008)
Aim: Our aim in this study is to evaluate the effect of ethanol as a sclerosing agent on subset of pediatric patients with prolonged rectal prolapse. Materials and Methods: From 1997 to 2003, 165 cases of primary rectal prolapse were treated by submucosal injection of ethyl alcohol (96%) after 8 weeks of conservative therapy. Around 1.5-2 ml of alcohol was linearly injected in three sites (two laterals and one posterior). Results: Twelve of the 165 cases lost the follow-up and 153 cases were followed from 9 months to 6 years. One hundred and six patients (69.3%) had a duration of prolapse for 3-7 months. Forty patients (26.1%) had prolapse for more than 7 months and seven patients had prolapse for more than 1 year. One hundred and forty-seven out of 153 (96%) patients responded to single injection. Three of the children required a second injection. Three patients with age of more than 13 did not respond to the treatment. Twenty five cases had fecal soilage for few days. No infectious complication and no recurrence were observed. Conclusion: We concluded that 4-6 ml of ethyl alcohol (96%) is effective for the treatment of rectal prolapse. The duration of rectal prolapse had no deleterious effect on treatment; however, patients with age more than 13 years did not respond to sclerosing agent, probably due to different etiology.